Result of ESWL in the Management of Urinary Stones, in the Department of Urology, Chittagong Medical College Hospital: A Study of 500 Cases - Hossain, Mohammed Jahangir; Uddin, Md Nizam; Islam, Md Saiful (Journal of Chittagong Medical College Teachers' Association, 2010)
Key words: ESWL; Urinary stones DOI: 10.3329/jcmcta.v20i1.4935 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):45-49